Fleas on Operations in Afghanistan – Environmental Health Measures on the Front Line. Issue 3 (1st September 2011) - Naumann, DN; Baird-Clarke, CD; Ross, DA
Abstract : Flea bites can cause irritating symptoms, secondary infections, and may potentiate the spread of vector-borne disease. Flea infestation and bites may also cause significant psychological distress, and can reduce the morale and fighting fitness of deployed military personnel. The problem of flea infestation was highlighted during Op HERRICK 12 in two 'front line' Check Points (CPs) where the entire population of soldiers suffered from multiple symptoms due to flea infestation and bites. Several attempts at infestation control initially succeeded but later lead to recurrence. Such failure was due to the incomplete killing of all stages of the flea life cycle, and due to constraints on education, training, communication, and resupply in the isolated and austere environment of the CPs. A dedicated operation (designated Op Insecticide) was put into action in order to eradicate the problem and return the affected troops back to full fighting fitness. Op Insecticide was thorough, systematic and sustainable, and lead to an eradication of the flea infestation problem at the affected CPs.